ANTIBACTERIAL EFFECTIVENESS TEST OF KERSEN LEAVES (MUNTINGIA CALABURAL L) ON ESCHERICHIA COLI - Sarita Ardila; Abdul Wahab; Aditya Candra (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2023)
The plant known as kersen leaf (Muntingia calabura L) is quite widespread in tropical regions and is frequently used by the local population as a traditional antibacterial because it has a number of pharmacological properties, one of which is the ability to kill Escherichia coli germs. The purpose of this study is to ascertain whether cherry leaf extract (Muntingia calabural L) inhibits Escherichia coli growth and whether cherry leaf extract (Muntingia calabural L) has an antibacterial impact on Escherichia coli. This study tested the ethanol extract of cherry leaves (Muntingia calabural L) against Escherichia coli bacteria using an experimental laboratory method. The collected data were examined using nonparametric statistical analysis known as ANOVA. According to the results of the phytochemical research, Kersen leaves contain tannins and saponins but no flavonoids. Escherichia coli antibacterial studies revealed that kersen leaf extract has a growth-inhibiting impact on these germs. As the concentration of the extract increased, a larger inhibition zone formed. Kersen leaves contain tannins and saponins, and the extract from these leaves can be used to treat bacteria such as Escherichia coli.